Sustainability, innovative orientation and export performance of manufacturing SMEs: An empirical analysis of the mediating role of corporate image - Francisco Villena; Jaime Eduardo Souto-Pérez (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: The objective of this research is to empirically analyze the role played by corporate image, sustainability, and innovative orientation on export performance. Design/methodology/approach: hypothesis testing was conducted with a sample of 180 manufacturing SMEs in Seville (Spain) and a structural equation system is modeled using the technique Partial Least Squares (PLS). The research model includes the following variables: corporate image, sustainability, and innovative orientation on export performance. Findings: The results show the positive effect of sustainability and innovative orientation on export performance, as well as the mediator effect of corporate image on these relationships. Research limitations/implications: The results may be more general if we had used a national sample and cross cultural. The conclusions cannot be directly extrapolated to other countries. This work propose future research doing the same study with other types companies. Originality/value: Corporate image requires special attention, as it acts as a filter of the impacts of sustainability and innovative orientation. The creation of corporate image not only as a result of tangible items, but as a result of the actions and behavior of the company. In this research is showed that there is a high level of complexity in the management of intangibles since the intangibles influence each other, such as the influence of sustainability and innovative orientation on corporate image. Managers should focus on proper design and management of the company image, in order to compete and grow in the international area.
Keywords: 650; corporate image; sustainability; innovative orientation; exports performance